Predictors of adverse drug reaction-related hospitalisation in Southwest Ethiopia: A prospective cross-sectional study - Angamo, Mulugeta Tarekegn; Curtain, Colin Michael; Chalmers, Leanne; Yilma, Daniel; Bereznicki, Luke (PloS one, 2017)
Adverse drug reactions (ADRs) are important causes of morbidity and mortality in the healthcare system; however, there are no studies reporting on the magnitude and risk factors associated with ADR-related hospitalisation in Ethiopia. To characterise the reaction types and the drugs implicated in admission to Jimma University Specialized Hospital, Southwest Ethiopia, and to identify risk factors associated with ADR-related hospitalisation. A prospective cross-sectional study was conducted from May 2015 to August 2016 among consenting patients aged ≥18 years consecutively admitted to medical wards taking at least one medication prior to admission. ADR-related hospitalisations were determined through expert review of medical records, laboratory tests, patient interviews and physical observation. ADR causality was assessed by the Naranjo algorithm followed by consensus review with internal medicine specialist. ADR preventability was assessed using Schumock and Thornton's criteria. Only definite and probable ADRs that provoked hospitalisation were considered. Binary logistic regression was used to identify independent predictors of ADR-related hospitalisation. Of 1,001 patients, 103 (10.3%) had ADR-related admissions. Common ADRs responsible for hospitalisation were hepatotoxicity (35, 29.4%) and acute kidney injury (27, 22.7%). The drug classes most frequently implicated were antitubercular agents (45, 25.0%) followed by antivirals (22, 12.2%) and diuretics (19, 10.6%). Independent predictors of ADR-related hospitalisation were body mass index (BMI) <18.5 kg/m2 (adjusted odd ratio [AOR] = 1.69; 95% confidence interval [CI] = 1.10-2.62; p = 0.047), pre-existing renal disease (AOR = 2.84; 95%CI = 1.38-5.85, p = 0.004), pre-existing liver disease (AOR = 2.61; 95%CI = 1.38-4.96; p = 0.003), number of comorbidities ≥4 (AOR = 2.09; 95%CI = 1.27-3.44; p = 0.004), number of drugs ≥6 (AOR = 2.02; 95%CI = 1.26-3.25; p = 0.004) and history of previous ADRs (AOR = 24.27; 95%CI = 11.29-52.17; p<0.001). Most ADRs (106, 89.1%) were preventable. ADRs were a common cause of hospitalisation. The majority of ADRs were preventable, highlighting the need for monitoring and review of patients with lower BMI, ADR history, renal and liver diseases, multiple comorbidities and medications. ADR predictors should be integrated into clinical pathways and pharmacovigilance systems.